FACTORS AFFECTING THE EFFECTIVENESS OF SCHOOL UNDER THE OFFICE SECONDARY EDUCATIONAL SERVICE AREA 9 - ดนตรีพงษ์ ทิพมาศ; รักงาม ชัยพจน์; ชำนาญ สมุทร (Academic Journal Phranakhon Rajabhat University, 2018)
The purposes of this study were to study the effectiveness level of school, to study the relationship and factors affecting the effectiveness of school and to develop prediction equations for the effectiveness of school. Samples were 338 teachers under the Office of Secondary Educational Service Area 9 by stratified random sampling as size of school. Instrument used in data collection was 5 levels Rating Scale questionnaire with 4 sections, namely, questionnaire on the effectiveness of school, change leadership of school administrator, organizational atmosphere of school and performance motivation of teachers with discrimination power between .28-83, reliability of .90, .94, .85 and .96 respectively. Data analysis used computer program. Statistics used in data collection were mean (X), standard deviation (S.D.), Pearson’s product moment correlation and stepwise multiple regression analysis. The results of research found that: 1. The factors level of change leadership of administrator, organizational atmosphere of school and performance motivation of teachers in the Office of Secondary Educational Service Area 9 on the whole and each aspect were at much level. 2. The relationship between change leadership factors of administrator organizational atmosphere of school and performance motivation and effectiveness significant positive relationship at high level of .01 3. Change leadership factors, organizational atmosphere of school and performance motivation of teachers affected to statistically significant effectiveness of school under the Office of Secondary Educational Service Area 9 at level of .05 4. Prediction factors for the factors affecting the effectiveness of school under the Office of Secondary Educational Service Area 9 had statistically significant ability to predict with 81.20 percents at level of .05 by writing in form of raw scores equations as follows: Y = .853 + .419 (X11) + .124 (X21) + .139(X22) + .110 (X35) -.086 (X14) + .098 (X31) Or prediction equation in form of standard scores as: Z = .564 (Z11) + .147 (Z21) + .190 (Z22) + .171(Z35) -.124 (Z14) + .106 (Z31)